PM.49 Reproductive Loss from a Multiple Pregnancy: Health Professionals' Perspectives. (26th April 2013) - Richards, J; Graham, R; Embleton, N; Robson, S; Rankin, J
Abstract : Objective: To provide an in-depth understanding of the experiences of health professionals who care for parents who have had a loss from a multiple pregnancy. Method: A qualitative study involving semi -structured interviews. Participants were recruited from two NHS Tertiary hospital units: a Critical Care Baby Ward and Fetal Medicine department. 26 health professionals from a range of clinical roles were interviewed. Data were analysed using a generative thematic approach. Results: Whilst all health professionals felt confident in administering medical care, they felt less confident when dealing with the bereavement issues of parents who may spend many months in hospital whilst surviving multiples are cared for. Staff often felt that they were 'second guessing' what parents' needs might be and feared 'saying the wrong thing' within daily interactions with parents. Conclusion: Many staff, particularly those in more junior roles, felt that they would benefit from formal bereavement training in order to understand more fully how to react effectively to parents' emotional needs. Staff also felt they lacked information regarding the formal bereavement services available to parents and were unsure as to when it was appropriate to utilise them. The value of experience was also acknowledged however, alongside the need for flexibility of approach in order to react to the specific needs of parents.